Simulation of subsea production pipeline stream to evaluate and address the flow assurance issues of waxy crude oil - Ahmed, Ashfaq (Curtin University, 2009)
The modern world is heavily dependent on crude oil and its associated products and the petroleum industry has taken responsibility to meet the rising consumer demand. Oil and gas production can be broadly subdivided into three separate fields of science and technology, notably production processes in the reservoir, production of oil and gas from the wells and finally surface gathering, separation and transportation.This research focused on the problem that oil producers usually face with waxy crude oil during its production, processing and transportation. Wax build up, especially in the crude oil production pipeline, is the key task for the operators to deal with as it may cease crude flow through the pipeline and associated production facilities. Research efforts to date, have addressed flow assurance issues of crude oil displacement through the production pipeline and processing facilities but further research is needed to determine the best outcome to cope with situation.The principal objective of this research is to simulate crude flow through the production pipeline using hydrocarbon simulation software Aspentech HYSYS 3.2 and PIPESYS to investigate the root cause and analyse flow assurance issues with the aim of elimination of such issues through the production pipeline. The simulation focused on the study of crude oil properties including temperature, pressure and viscosity affecting the crude oil flow from the reservoir or through the production pipeline, and the results compared with normal operating conditions of the wellhead and production pipeline.Three different scenarios involving the detailed study of temperature and pressure were simulated at temperatures and pressures above or below the normal operating condition reference points.The simulation results reveal that the crude oil flow through the production pipeline predominantly decreases due to a gradual drop of temperature along the cumulative length of the pipeline. The viscosity of the crude oil accordingly increases with the drop in temperature, which consequently reduces the flowrate of crude oil through the pipeline. Conversely, an increment in crude oil production is obtained with an increase in crude oil temperature from 60 ºC to 65 ºC. Moreover, there is no direct significant effect on the viscosity of crude oil with an increase or decrease in pressure compared to normal operating conditions. However, a significant drop in production is observed with the drop in temperature and pressure below the normal operating temperature and pressure of the pipeline.The outcome of this study will enable design engineers to understand the complications which usually occur while operating such facilities and give special consideration to those issues at the detailed engineering design stage of future similar facilities.